Personal Branding Content Creator Arif Muhammad (Analisis Visual pada Akun Youtube @Arif Muhammad) - Amalia, Tri Wahyu; Satvikadewi, A.A.I. Prihandari (representamen, 2020)
The emergence of more content creator, is the impact of social media development, especially youtube. Youtube became the most accessible platform on 2019. It requires content creators to create quality content and form personal branding, so they can compete and get recognition. This research will reveal the personal branding of a youtube content creator, namely Arif Muhammad or Mak Beti, who is trending on youtube because of his comedy content as a multirole. This qualitative study examines one video on @Arif Muhammad's youtube account, titled "Beti Pergi ke Mall", where in the video Arif played 15 characters. The study uses the visual methodology by Gillian Rose, from three areas of visual research, site of self, site of production, and site of audience. The results showed that personal branding of Arif Muhammad through the video in his youtube account, found 7 out of 8 main concepts of personal branding by Peter Montoya namely, Specialization, Leadership, Personality, Distinctiveness, Visibility, Persistance, and Goodwill. The law of strength is specialization. Personal Branding of Arif Muhammad make him called as The King of Youtube and King of Trending by his audience. Keywords: personal branding, content creator, youtube